If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 21 = -42x + -6 Reorder the terms: 21 + 2x = -42x + -6 Reorder the terms: 21 + 2x = -6 + -42x Solving 21 + 2x = -6 + -42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42x' to each side of the equation. 21 + 2x + 42x = -6 + -42x + 42x Combine like terms: 2x + 42x = 44x 21 + 44x = -6 + -42x + 42x Combine like terms: -42x + 42x = 0 21 + 44x = -6 + 0 21 + 44x = -6 Add '-21' to each side of the equation. 21 + -21 + 44x = -6 + -21 Combine like terms: 21 + -21 = 0 0 + 44x = -6 + -21 44x = -6 + -21 Combine like terms: -6 + -21 = -27 44x = -27 Divide each side by '44'. x = -0.6136363636 Simplifying x = -0.6136363636
| cos(2x)+5sinx+2=0 | | 7x-86=180 | | 1-3x=49 | | 1-3x=48 | | 4y=24+2x | | 1.2+0.3=7.5 | | 3d^2-d-4=0 | | 9x-48=x | | Cosx=cord | | 80-x=4x-30 | | 2x+y=560 | | x+25+2x-20=110 | | 4x-6+5x+15=180 | | 360-305= | | 90+90+125= | | 10x-48=180 | | 215+125= | | 215+65= | | 55+215= | | 360-215= | | 2x+10=108 | | 215-180= | | 11x-3x=48 | | 125+90= | | -4x=3+-2x+8 | | Logt=2.8 | | 100*log(x)=4 | | 100*log(x)=-1 | | p-3=6p-28 | | 100*log(x)=0 | | -3x+3=10x+15 | | x=(6x+12) |